(untitled) (Journal of Lithic Studies, 2016)
In recent years, allusions to exploitation of a so-called “Monegros-type” chert have been a commonplace in archaeological literature, mostly in Iberia but also in southern France. It has been also a routine that these references did not include a true petrographic characterization, being mere de visu descriptions of those products. This work presents, for the first time, macro and microscopic characterizations of some of the most outstanding chert outcrops located in the Middle Ebro Basin. There, tertiary limestone sediments that form the top part of the flat plateau reliefs hold great quantities of chert nodules. The noteworthy erosive processes that have affected this area have facilitated the gathering of those cherts: they are easy to find either in their original location, still embedded in the limestone layers, or in secondary position along the enormous glacis that connect those flat reliefs to the river terraces. Two main flint varieties have been defined: Monegros and Evaporitic of Ebro. Both were originated in continental lacustrine environments. They are fine-grained and offer excellent knapping possibilities; hence its common use since prehistoric times to recent semi-industrial exploitations related to 18th century gunflint productions. This paper offers a preliminary study that will be developed in a forthcoming PhD dissertation, but we also include examples of its prehistoric exploitation in the Ebro Basin and abroad.